Model Perilaku Penggunaan Quick Response Code Indonesian Standard (QRIS) Masyarakat Tangerang dengan Pendekatan Technology Acceptance Model (TAM) - Monika Palmalita Hutasoit; Sugiyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
COVID-19 has created a demand for contactless technology, in line with the significant technological growth in Indonesia. Contactless or cashless payment technology has become the preferred payment method as it eliminates the need for physical contact with paper money, coins, or even other people's hands. As an innovation, the Government has responded to this challenge by supporting the National Payment Gateway (GPN) regulation, and Bank Indonesia has established a national standard code known as QRIS. This study aims to determine the extent to which system users perceive the system as useful (Perceived Usefulness), easy to use (Perceived Ease of Use), and to understand how Behavioral Intention and social influence in the user's environment can affect their attitude and behavior towards system usage (Actual System Use) using the TAM approach in the Tangerang Regency area. Data collection was conducted through an online questionnaire distributed in June 2024. Data analysis in this study used the Partial Least Square (SEM PLS) method with a sample size of 165 respondents. The data processing results indicate that factors such as Perceived Usefulness and Perceived Ease of Use have a significant positive influence on Behavioral Intention and Actual System Use in the use of QRIS. Perceived Usefulness and Perceived Ease of Use affect Actual System Use through Behavioral Intention. Meanwhile, social influence does not significantly affect Actual System Use through Behavioral Intention. The managerial implications of this study suggest that Bank Indonesia should enhance the security and reliability of the QRIS system to build public trust and confidence in this digital payment system. Additionally, the registration and usage processes for QRIS should be simplified to ensure they are easily understood and used by all segments of the population, including those less familiar with technology. These measures are expected to increase public adoption and trust in QRIS as a digital payment system